2016
DOI: 10.1177/1075547016642241
|View full text |Cite
|
Sign up to set email alerts
|

Citizen Science

Abstract: Citizen science can raise people's understanding of science while helping scientists conduct their research. Yet its potential for driving transformative learning is empirically underexplored. We present the results of a preliminary study with secondary school students engaged in a long-term citizen science project, from the formulation of the research questions to data analysis and discussion. Students learnt about and increased their interest in neuroscience. They were also able to reflect on the role of sci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 13 publications
2
27
0
2
Order By: Relevance
“…The students described multiple ways that participation led to an increase in their interest and resulted in diverse learning outcomes. Our findings are also in line with previous studies that highlight the potential of participating in citizen science projects during school time as a way of increasing personal interest in science (Hiller and Kitsantas 2014; Ruiz-Mallén et al 2016).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The students described multiple ways that participation led to an increase in their interest and resulted in diverse learning outcomes. Our findings are also in line with previous studies that highlight the potential of participating in citizen science projects during school time as a way of increasing personal interest in science (Hiller and Kitsantas 2014; Ruiz-Mallén et al 2016).…”
Section: Discussionsupporting
confidence: 92%
“…Citizen science can involve lifelong participation and sophisticated research skills, or it can be short-term with no specific skills required to participate (Shirk et al 2012). Public participation in science has been suggested to lead to a better understanding of science and scientific processes and foster positive attitudes towards science (Ruiz-Mallén et al 2016; Phillips et al 2018; Bonney et al 2016). Furthermore, the research literature suggests that doing research in one’s own near environment (i.e., environment in which a person lives or works) nurtures positive attitudes toward the environment, and specifically the studied species (McKinley et al 2017; Ballard, Dixon, and Harris 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Unexpectedly, we found that such checks are necessary even for data acquired by professional scientists. It must be kept in mind that thrill, motivation, and self-confidence are keys to school children engagement with science and with practical scientific activities 20,37 . Our findings that school children did no worse than untrained professional scientists in collecting ecological data (here, in estimating insect herbivory) can strengthen their confidence and help them gain motivation and a positive attitude toward science in general.…”
Section: Discussionmentioning
confidence: 99%
“…Both studies provided an overview of the current situation of citizen science from a research context point of view. Regarding the aim of this work, Follet and Strezov [20] analyse the classification of [29] who identifies a type of citizen science projects developed as education projects that are often performed in the classroom or school grounds as part of the science curriculum, such as [30][31][32][33].…”
Section: Related Workmentioning
confidence: 99%